Implementasi Pusat Pelayanan Usaha Terpadu (PLUT) dalam Pemberdayaan UMKM di Kota Batam - Latifa Nur Fajriyah; Afrizal Afrizal; Uly Sophia (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
Empowerment is the process of increasing the capacity and independence of individuals and groups so they can develop optimally. Empowerment of UMKM is important because of their strategic role in supporting national economic growth. However, UMKM still face various problems such as legality, capital, marketing, and managerial skills. To support this effort, PLUT was established at the initiative of the Batam City Government to encourage UMKM to move up a class. PLUT Batam City plays an important role through strategic services such as consulting, business mentoring, legal facilitation, training, product and packaging development, as well as promotion and marketing. This study uses a qualitative method with interview, observation, and documentation techniques. The theory used is the Van Meter and Van Horn implementation model which includes six variables: policy objectives, resources, communication, implementer characteristics, socio-economic conditions, and implementer attitudes. This study aims to analyze the implementation of the PLUT program in empowering UMKM in Batam City.